Neural stem cell research in Africa: current realities and future prospects - Azeez, Idris A.; Awogbindin, Ifeoluwa O.; Olayinka, Juliet N.; Folarin, Royhaan O.; Adamu, Abubakar S.; Ior, Lydia D.; Kamoga, Ronald; Usende, Ifukibot L. (Biology Open, 2022)
Neural stem cells (NSCs) are immature progenitor cells that are found in developing and adult brains that have the potential of dividing actively and renewing themselves, with a complex form of gene expression. The generation of new brain cells in adult individuals was initially considered impossible, however, the landmark discovery of human neural stem cells in the hippocampus has been followed by further discoveries in other discreet regions of the brain. Investigation into the current state in Africa of the research and use of NSCs shows relatively limited activities on the continent. Information on the African application of NSCs for modelling disease mechanisms, drug discovery, and therapeutics is still limited. The International Brain Research Organization (IBRO)-African Regional Committee (ARC), with support from the Company of Biologists, and the Movement Disorder Society, sponsored the first African Basic School on NSC in Ibadan, Nigeria, with the vision of bringing together young neuroscientists and physicians across different fields in neuroscience to learn from leaders who have applied NSCs in stem cell research, the pathophysiology of neurodegenerative diseases, neuroanatomy, and neurotherapeutics. Twenty early-career researchers in academic institutions at junior and senior faculty cadres were selected from South Africa, Uganda and Nigeria. The students and organizer of the school, who wrote this review on the state of NSCs research in Africa, recommended the following: (1) other African countries can take a cue from South Africa and Nigeria in probing the phenomena of adult neurogenesis in unique animal species on the continent; (2) Africa should leverage the expertise and facilities of South African scientists and international collaborators in scaling up NSC research into these unique species and (3) Centers of Excellence should be established on the continent to serve as research hubs for training postgraduate students, and facilities for African scientists who trained overseas on NSCs.
Keywords: Neural stem cells; Brain research; Africa; Adult neurogenesis